Eliciting brain waves of people with cognitive impairment during meditation exercises using portable electroencephalography in a smart-home environment: a pilot study - Lazarou, Ioulietta; Oikonomou, Vangelis P.; Mpaltadoros, Lampros; Grammatikopoulou, Margarita; Alepopoulos, Vasilis; Stavropoulos, Thanos G.; Bezerianos, Anastasios; Nikolopoulos, Spiros; Kompatsiaris, Ioannis; Tsolaki, Magda; , RADAR-AD Consortium (Frontiers in Aging Neuroscience, 2023)
Objectives: Meditation imparts relaxation and constitutes an important non-pharmacological intervention for people with cognitive impairment. Moreover, EEG has been widely used as a tool for detecting brain changes even at the early stages of Alzheimer’s Disease (AD). The current study investigates the effect of meditation practices on the human brain across the AD spectrum by using a novel portable EEG headband in a smart-home environment. Methods: Forty (40) people (13 Healthy Controls - HC, 14 with Subjective Cognitive Decline - SCD and 13 with Mild Cognitive Impairment - MCI) participated practicing Mindfulness Based Stress Reduction (Session 2-MBSR) and a novel adaptation of the Kirtan Kriya meditation to the Greek culture setting (Session 3-KK), while a Resting State (RS) condition was undertaken at baseline and follow-up (Session 1- RS Baseline and Session 4- RS Follow-Up). The signals were recorded by using the Muse EEG device and brain waves were computed (alpha, theta, gamma and beta). Results: Analysis was conducted on four-electrodes (AF7, AF8, TP9 and TP10). Statistical analysis included the Kruskal–Wallis (KW) nonparametric analysis of variance. The results revealed that both states of MBSR and KK lead to a marked difference in the brain’s activation patterns across people at different cognitive states. Wilcoxon Signed-ranks test indicated for HC that theta waves at TP9, TP10 and AF7, AF8 in Session 3-KK were statistically significantly reduced compared to Session 1-RS Z=-2.271, p= 0.023, Z= -3.110, p= 0.002 and Z= -2.341, p= 0.019, Z= -2.132, p= 0.033 respectively. Conclusions: The results showed the potential of the parameters used between the various groups (HC, SCD and MCI) as well as between the two meditation sessions (MBSR and KK) in discriminating early cognitive decline and brain alterations in a smart-home environment without medical support.